Behavioral Intention of the Use of COVID-19 Governance Application: A Literature Review - Yoserizal, Yoserizal; Tovalini, Krismena; Hanoselina, Yulia (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2024)
The COVID-19 pandemic has had a profound impact on Indonesia, affecting not only public health but also socio-economic aspects of life. As part of its response to mitigate the spread of the virus, the Indonesian government introduced the PeduliLindungi application, which enables contact tracing and monitoring of COVID-19 cases through public participation. Despite its effectiveness in supporting policy decisions and reducing transmission rates, the application has faced criticism, particularly regarding potential privacy and human rights concerns. This study aims to analyze the behavioral intention of users to adopt the PeduliLindungi application using the Technology Acceptance Model (TAM) as a framework. The research employs a literature review approach, synthesizing findings from existing studies to identify key factors influencing user attitudes and intentions. Results indicate that perceived usefulness, perceived ease of use, and perceived risk are critical determinants of user attitudes. Furthermore, the study hypothesizes that user attitudes significantly influence behavioral intention, with trust in the application playing a reciprocal role. The findings highlight the importance of addressing user concerns, particularly regarding data security and privacy, to enhance adoption rates. This research contributes to the understanding of user behavior in adopting COVID-19 governance applications and provides a theoretical basis for future empirical studies. It concludes with recommendations for policymakers to ensure both the efficacy and ethical implementation of such technologies in public health crises.